Synthesis and characterization of copper nanoparticle of Solanum Virginianum and Coccinia Grandis extract: A comparative study of thermal behavior - Muthuselvi Raghunathan; Prema Anbarasu; Vashantha Ramaswami (Zaštita Materijala)
A Biogenic, green synthesis method is described for the novel copper nanoparticles from the leaf extract of Solanum Virginianum and Coccinia Grandis. Fourier-Transform Infrared spectroscopy and Thermal gravimetric analysis were used to examine the resultant nanoparticles. Compositional analysis and the study of processes like vaporization and decomposition were both accomplished by thermogravimetric analysis. The volatile compounds that the sample released was analyzed using TGA in conjunction with Fourier transform infrared spectroscopy (FTIR). From the FTIR data obtained it showed that the CG-CuNPs and SV-CuNPs both included functional molecular structure. Additionally, the TGA results showed that SV-CuNPs and CG-CuNPs exhibit effective thermal stability behavior, while the plant extracts from Coccinia grandis and Solanum virginianum play a major role in the creation of nanoparticles and also enhance their thermal stabilities.